2020
DOI: 10.1097/scs.0000000000007147
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Auricular Calcinosis Cutis

Abstract: To the Editor: Calcinosis cutis (CC) is a rare disease characterized by abnormal accumulation of insoluble calcium phosphate crystals in skin and subcutaneous tissues. 1 It is classified in 4 types as etiologically dystrophic, metastatic, iatrogenic, and idiopathic. 2 It is important to determine the type of calcinosis for proper treatment management. Dystrophic type CC is most common. Idiopathic CC is characterized by normal serum calcium and phosphorus. Idiopathic CC, which is the rarest type, is characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Local inflammation (that stands as a contributor/trigger to calcium deposits) may be found at pathological report, typically in dystrophic rather than metastatic cases. Calcification in petrified ears should be distinguished from isolated nodules found in calcinosis cutis, which is more common in pediatric populations [ 75 , 76 , 77 ]. Some authors suggested that calcification may turn into ossification amid the local action of different triggers such as trauma or frostbite [ 4 ]; thus poly-factorial etiology may be present.…”
Section: Petrified Earsmentioning
confidence: 99%
“…Local inflammation (that stands as a contributor/trigger to calcium deposits) may be found at pathological report, typically in dystrophic rather than metastatic cases. Calcification in petrified ears should be distinguished from isolated nodules found in calcinosis cutis, which is more common in pediatric populations [ 75 , 76 , 77 ]. Some authors suggested that calcification may turn into ossification amid the local action of different triggers such as trauma or frostbite [ 4 ]; thus poly-factorial etiology may be present.…”
Section: Petrified Earsmentioning
confidence: 99%